The international literature underpinning collaborative practice within practice based experiential learning for the initial education of student pharmacists: a scoping review. (26th March 2021) - Jebara, T; Depasquale, C; Power, A; Boyter, A; Portlock, J; Cunningham, S
Abstract: Introduction: Interprofessional team working within healthcare [1] enables the use of complementary areas of expertise. Collaborative practice (CP) builds on this and enhances recognition and respect for such expertise which facilitates professional synergy. Development of CP needs to be built into initial education programmes and there is global progress. [2] Further, a WHO Framework highlighted the importance of courses developing CP in experiential learning (EL) environments. [1] There is need to develop both CP and EL within pharmacy courses to meet governmental and regulatory aspirations around the clinical and prescribing roles of pharmacists. Aim: The aim of this part of a scoping review was to describe the different characteristics of the international literature around the development, implementation and evaluation of CP within practice based EL for initial education of student pharmacists. Methods: The six-stage Arksey and O'Malley framework and the PRISMA extension for Scoping Reviews for reporting were followed. Eligibility criteria were defined (Table 1) and electronic searches of relevant databases (Medline, IPA, CINAHL and Google Scholar) conducted from inception to April 2020. MeSH terms and other relevant subject headings and text words were used. First stage involved screening titles / abstracts and second stage involved review of full text articles. A charting tool was developed and used to extract data on: country, study design, methods of evaluation, sector of practice, stage of students, professional groups involved, monitoring and assessment and scope for development. Findings were presented as a descriptive narrative summary. All steps involved independent checks by two of the review team. Results: Twenty-eight papers were included with most from the USA (16 papers), with the remainder from Australia (5 papers), UK (5 Papers), Canada and the Netherlands (1 paper each). The majority of papers described quantitative methods using a wide variety of published (some validated) scales (20 scales including RIPLS, SPICE, CPAT) and a number of bespoke survey tools. The main focus was at 'Kirkpatrick model of educational evaluation' level 3 – with 13 papers focussing on changes to professional behaviours. Papers focussed on either hospital (12 papers) or primary care initiatives (12 papers) with the remaining four describing cross-sectoral settings. Only 6 papers stated that they focussed on specific healthcare specialities and the remainder were in general medical facilities. The nature of initiatives and activities varied with a predominance of focus to include later years of study. Only 3 papers included only pharmacy and medicine students.. Detailed information was lacking on methods of student assessment: some reported this involved reflection, with limited reporting of tools to assess competencies. A wide array of further research proposals was articulated. Conclusion: This scoping review highlights the range of work already carried out. The diversity highlights the need for consideration of commonality in the nature of activity and tools to evaluate outcomes to ensure transferability to practice. There are many challenges influencing further development and implementation of CP. Facilitating matters by using the evidence base to add to existing placements without restructuring curricula across courses / institutions has been proposed by some authors. References: 1. Framework [Framework for Action on Interprofessional Education & Collaborative Practice (WHO/HRH/HPN/10.3). World Health Organization 2010, Geneva 27, Switzerland, Available at http://www.who.int/hrh/nursing_midwifery/en/ [Accessed 4 Aug 2020] 2. Barr H. Interprofessional Education-The Genesis of Global Movement. 2015. https://www.caipe.org/resources/publications/barr-h-2015-interprofessional-education-genesis-global-movement . [Accessed 4 Aug 2020]